Jusqu’où faut-il aller trop loin : Charles Reade, une esthétique de l’excès - Laurent Bury (Cahiers Victoriens et Edouardiens)
Charles Reade, the novelist (1814-1884), has lain in purgatory for more than one century, apparently because of his taste for excess. Rehabilitation is still to come for the author of It Is Never Too Late to Mend (1856), The Cloister and the Hearth (1861) or Hard Cash (1863), the three works which are studied in this paper. Reade never knew how to check his productivity, as exemplified by the constant recycling of his own texts and others’, his desire to shock the Victorian public with bloody episodes, or his decision to leave nothing unsaid, at the risk of crushing his readers under an excessive mass of words.